A practical theology case study of transforming lives of the poor in the Amalinda Forest Community, East London - Dames, Gordon Ernest; Mazantsana, Mandah Khuthaza (Stellenbosch Theological Journal, 2024)
How can the problem of poverty be addressed by those concerned about the transformational development of the poor in South Africa? The church, as a community of faith and the bearer of the Christian witness cannot be left behind when responding to this question. This article reflects on a practical theological intervention where a church moved beyond its walls to help those in need. The active role played by the church in addressing this problem and the response of the community will be brought to light. However, this is a challenge that does not affect a local church only: research findings undergird the transformative engagement of the entire church community and calls for local social and political institutions to form a multipurpose partnership to deal with poverty in affected communities.